Expression of Stem Cell Markers in Preinvasive Tubal Lesions of Ovarian Carcinoma. (4th October 2015) - Chene, G.; Ouellet, V.; Rahimi, K.; Barres, V.; Meunier, L.; De Ladurantaye, M.; Provencher, D.; Mes-Masson, A. M.
Abstract : In order to better understand the ovarian serous carcinogenic process with tubal origin, we investigated the expression of stem cell markers in premalignant tubal lesions (serous tubal intraepithelial carcinoma or STIC). We found an increased stem cell marker density in the normal fallopian tube followed by a high CD117 and a low ALDH and CD44 expression in STICs raising the question of the role of the stem cell markers in the serous carcinogenic process.